Women’s Role in Nepal in General and Population Control in particular - An Assessment - Shrestha, Maheshorman; Shrestha, Sudha (Tribhuvan University Journal, 2010)
The basis for an effective solution of population problems is, above all, socio-economic transformation. Key words: Women's role in Nepal; Male and female elements Tribhuvan University Journal Volume XIV, 1991 Page: 27-41 Uploaded date: 5 October, 2010